Determinants of Mudharabah Deposits in Islamic Rural Banks in Indonesia: Evidence from the 2020–2024 Period - Salma Noor Khalifatuzzahra; Moh Mukhsin; Ahmad Fatoni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Abstrack This study aims to analyze the determinants of mudharabah deposits at Islamic Rural Banks (BPRS) in Indonesia for the period 2020–2024. The variables used include Islamic Rate of Return, conventional bank deposit rates, inflation, and money supply, using monthly secondary data across four deposit maturities — one month, three months, six months, and twelve months. The analytical methods employed are the Autoregressive Distributed Lag (ARDL) for one-month, three-month, and twelvemonth maturities, and the Error Correction Model (ECM) for the six-month maturity. The results indicate that the influence of the four variables is heterogeneous — varying in direction and significance depending on the maturity and time horizon of the analysis. Simultaneously, all four variables have a significant effect in the long run but are not significant in the short run. Among the four variables, money supply is the most dominant and consistent factor influencing mudharabah deposits across all maturities in the long run, while the influence of the other variables is selective across specific maturities and time horizons. These findings imply that depositors' decisions to place funds cannot be explained by a single factor, but are influenced by a combination of Islamic banking internal factors and macroeconomic conditions that operate differently across each maturity segment. Keywords: Mudharabah Deposits, Islamic Rate of Return, Deposit Interest Rate, Inflation, Money Supply, BPRS Abstrak Penelitian ini bertujuan menganalisis determinan deposito mudharabah pada Bank Perekonomian Rakyat Syariah (BPRS) di Indonesia periode 2020–2024. Variabel yang digunakan meliputi Islamic Rate of Return, suku bunga deposito bank umum konvensional, inflasi, dan jumlah uang beredar, dengan data sekunder bulanan pada empat tenor — satu bulan, tiga bulan, enam bulan, dan dua belas bulan. Metode analisis yang digunakan adalah Autoregressive Distributed Lag (ARDL) untuk tenor satu bulan, tiga bulan, dan dua belas bulan, serta Error Correction Model (ECM) untuk tenor enam bulan. Hasil penelitian menunjukkan bahwa pengaruh keempat variabel bersifat heterogen — berbeda arah dan signifikansi tergantung pada tenor dan horizon waktu analisis. Secara simultan, keempat variabel berpengaruh signifikan dalam jangka panjang namun tidak signifikan dalam jangka pendek. Di antara keempat variabel, jumlah uang beredar merupakan faktor paling dominan dan konsisten yang memengaruhi deposito mudharabah di seluruh tenor dalam jangka panjang, sementara pengaruh variabel lainnya bersifat selektif pada tenor dan horizon waktu tertentu. Temuan ini mengimplikasikan bahwa keputusan nasabah dalam menempatkan dana tidak dapat dijelaskan oleh satu faktor tunggal, melainkan dipengaruhi oleh kombinasi faktor internal perbankan syariah dan kondisi makroekonomi yang bekerja secara berbeda pada setiap segmen tenor. Kata kunci: Deposito Mudharabah, Islamic Rate of Return, Suku Bunga Deposito, Inflasi, Jumlah Uang Beredar, BPRS